Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
câu c:x^4-2x^3-x^2+x^3-2x^2-x+5x^2-10x-5=x^2(x^2-2x-1)+x(x^2-2x-1)+5(x^2-2x-1)=(x^2-2x-1)(x^2+x+5)
a)= \(\frac{-1}{xy}\)
b)\(\frac{3}{2x+6}\) - \(\frac{x-6}{2x^2+6x}\)= \(\frac{3x}{2x\left(x+3\right)}\)- \(\frac{x-6}{2x\left(x+3\right)}\)= \(\frac{2x+6}{2x\left(x+3\right)}\)= \(\frac{2\left(x+3\right)}{2x\left(x+3\right)}\)= \(\frac{1}{x}\)
c)\(\frac{1}{xy-x^2}\)- \(\frac{1}{y^2-xy}\)= \(\frac{1}{x\left(x-y\right)}\)- \(\frac{1}{-y\left(x-y\right)}\)= \(\frac{y}{xy\left(x-y\right)}\)- \(\frac{-x}{xy\left(x-y\right)}\)= \(\frac{y+x}{xy\left(x-y\right)}\)
nhớ tick nhé